PENGARUH MANAJEMEN LABA TERHADAP REAKSI PASAR DENGAN RISIKO PASAR SEBAGAI VARIABEL MODERASI - Mayuriidz, Rahardian Indra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2014)
This study aim to examine the impact of earning management practice on market reaction. Independent variable used in this study is market reaction which measured using cumulative abnormal return (CAR). Dependent variable used in this study is earning management which measured using proxy of discretionary accrual. This study was conducted on Manufacture companies which listed at Indonesia Stock Exchange (IDX). From population of 131 companies 69 companies were taken as sample. Sampling method used is through purposive sampling method. Companies criteria are a manufactur company during the year which publish sustainable annual report, using same currency on its financial report, had a complete information and also generate profits. The collected data is analyzed by ordinary least square regression analysis and f test after meet several test requirements and classic assumption. The result of the study shows that earning management practice have positive effect on market reaction. This result can be proved in f test with 5% significantly level. On the other hand this study also shows us that market risk have no significant influence on the correlation of earning management practice on market reaction. Keyword: earning management, market risk, market reaction, abnormal return